2010
DOI: 10.1080/10807039.2010.501230
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Ecological Risk Assessment of the Toxicological Risks fromExxon ValdezSubsurface Oil Residues to Sea Otters at Northern Knight Island, Prince William Sound, Alaska

Abstract: A comprehensive, quantitative risk assessment is presented of the toxicological risks from buried Exxon Valdez subsurface oil residues (SSOR) to a subpopulation of sea otters (Enhydra lutris) at Northern Knight Island (NKI) in Prince William Sound, Alaska, as it has been asserted that this subpopulation of sea otters may be experiencing adverse effects from the SSOR. The central questions in this study are: could the risk to NKI sea otters from exposure to polycyclic aromatic hydrocarbons (PAHs) in SSOR, as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 64 publications
1
65
1
Order By: Relevance
“…They concluded that infaunal foraging by sea otters in western Prince William Sound (PWS; Alaska), the distribution of sea otter pits in the intertidal zone, and the presence of SSOR in the vicinity of foraging areas demonstrate a potential pathway for sea otters to be exposed to the polycyclic aro matic hydrocarbons (PAHs) in SSOR. We reached the same conclusion in Harwell et al (2010a).…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…They concluded that infaunal foraging by sea otters in western Prince William Sound (PWS; Alaska), the distribution of sea otter pits in the intertidal zone, and the presence of SSOR in the vicinity of foraging areas demonstrate a potential pathway for sea otters to be exposed to the polycyclic aro matic hydrocarbons (PAHs) in SSOR. We reached the same conclusion in Harwell et al (2010a).…”
Section: Introductionsupporting
confidence: 73%
“…Their calculations resulted in a frequency of sea otters encountering SSOR of 10 times per year (range 2 to 24, n = 15) for females and 4 times per year (range listed both as 2 to 4 and 2 to 5, n = 4) for males. By comparison, the estimates of Harwell et al (2010a;their Table 2) were about 2 to 7 times per year, depending on the sea otter class (7 classes of sea otters were distinguished based on age and gender); consequently, the Bodkin et al (2012) estimates of the frequency of sea otter encounters with SSOR comport with our previously published estimates.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations